Functional Cognitive Disorder: diagnostic challenges, clinical features, and future directions in a misunderstood condition - Mavroudis, Ioannis; Petridis, Foivos; Franekova, Katerina; Visternicu, Malina; Rarinca, Viorica; Burlui, Vasile; Ciobica, Alin; Novac, Bogdan; Dobrin, Irina; Hogas, Mihai Marian; Bovari, Erica; Albert, Cristina; et al. (Frontiers in Aging Neuroscience, 2025)
Functional Cognitive Disorder (FCD), a condition marked by significant subjective cognitive complaints in the absence of identifiable neurological disease, is increasingly recognized as a distinct and underdiagnosed entity in clinical practice. This review synthesizes recent findings to clarify its diagnostic features, differentiate it from other cognitive syndromes such as mild cognitive impairment and dementia, and explore its psychological underpinnings. We examined longitudinal studies, meta-analyses, and clinical frameworks to identify patterns of symptom presentation, cognitive performance, and psychosocial factors. Findings reveal that FCD is characterized by inconsistent cognitive deficits, preserved functional independence, and heightened help-seeking behavior, often accompanied by anxiety, metacognitive dysfunction, and maladaptive beliefs about memory. Unlike neurodegenerative conditions, FCD follows a stable, non-progressive course and shows no evidence of conversion to dementia when accurately diagnosed. Enhanced clinical recognition and structured assessment approaches are crucial for improving diagnostic accuracy, minimizing patient distress, and avoiding unnecessary medical interventions. Further research is needed to standardize diagnostic criteria and develop targeted therapeutic strategies.